Oral manifestations of anemia in HIV/AIDS patients without ARV treatment - Hidayat, Wahyu; Dewi, Tenny Setiani; Wisaksana, Rudi (Padjadjaran Journal of Dentistry, 2017)
AbstractIntroduction: Acquired immunodeficiency syndrome (AIDS) is  a set of symptoms caused by decreases of the immune system that was infected by human immunodeficiency virus (HIV). Blood disorders often found in patient with HIV and associated with HIV infection. Mostly found disorders is anemia of chronic disease. The prevalence of anemia in HIV/AIDS patients reaches 70%. Oral manifestations of anemia are atrophy of the papillae on tongue, glossodynia, pallor, angular cheilitis, glossitis, aphthous ulcers/erosive lesions, candidiasis, and geographic tongue. There are many publications that uses anemia as indicator to determine the prognosis of HIV infection, thus the description of oral manifestation of anemia in the non-ARV HIV/AIDS patients is a necessity. The purpose of this study was to describe the oral manifestation of anemia in the non-ARV HIV/AIDS patients. Methods: The methods used were purposive random sampling. Samples were new HIV/AIDS patients who have not got antiretroviral (ARV) treatment. The study included 40 patients in Teratai Clinic Hasan Sadikin Hospital Bandung. Results: Oral manifestations of anemia were found amongst non-ARV HIV/AIDS patients, which were candidiasis in  37 patients, glossodynia in 28 patients, glossitis in 10 patients, and angular cheilitis in 1 patient. Conclusion: From the study found that oral manifestations of anemia that found in non-ARV HIV/AIDS patients were candidiasis, glossodynia, glossitis and angular cheilitis. HIV/AIDS patients with anemia needed to treat more intensive for better prognosis and quality of life.Keywords: Anemia, HIV/AIDS, Candidiasis, Glossitis, Glossodynia